Juridical Study on the Cancellation of Land Certificate by Proof of Power Endorsement in the Review of Law No. 5 of 1960 concerning the Basis of Agrarian Law (study of decision No. 3/G/2021/PTUN. BDG) - M Agung Purnama (Riviera Publishing, 2024)
This study discusses the cancellation of land ownership certificates based on evidence of verponding eigendom (BEV) in the framework of Indonesian Law, especially by Law No. 5 of 1960 concerning Agrarian Principles. The study aims to explore the legal basis, procedures, and implications of cancelling land certificates when administrative defects or court decisions have permanent legal force. The research method used is normative juridical with a descriptive approach, analyzing the Rule of Law and the case of Decision Number 3/G/2021/PTUN case. BDG. The study results show that the certificate can be cancelled if administrative, legal defects or the ratification of power are not by the procedure. In addition, court decisions have an essential role in determining the validity of certificates. The implications of this study show the importance of strengthening land administration in the National Land Agency (BPN) to increase legal certainty for landowners and reduce the potential for ownership conflicts in Indonesia.